Removal of Tetrachloroethylene from Aqueous Solutions by Adsorption on Clay Minerals - A. Gil; A. Elmchaouri; Y. El Mouzdahir; S.A. Korili (Adsorption Science & Technology)
The objective of this study was to assess the adsorption capacity of Moroccan stevensite for the removal of tetrachloroethylene from aqueous solutions. The mechanism of adsorption of tetrachloroethylene was studied in terms of pseudo-first-order and pseudo-second-order kinetic models by applying the Freundlich, Langmuir and Sips isotherm models to the equilibrium adsorption data. A maximum adsorption capacity of 284 mg/g at equilibrium was achieved, which indicates that the stevensite can be considered an efficient and suitable adsorbent for the removal of tetrachloroethylene from water systems and wastewaters.